2009
DOI: 10.1186/cc7771
|View full text |Cite
|
Sign up to set email alerts
|

Haemofiltration in newborns treated with extracorporeal membrane oxygenation: a case-comparison study

Abstract: IntroductionExtracorporeal membrane oxygenation is a supportive cardiopulmonary bypass technique for patients with acute reversible cardiovascular or respiratory failure. Favourable effects of haemofiltration during cardiopulmonary bypass instigated the use of this technique in infants on extracorporeal membrane oxygenation. The current study aimed at comparing clinical outcomes of newborns on extracorporeal membrane oxygenation with and without continuous haemofiltration.MethodsDemographic data of newborns tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 22 publications
2
59
0
Order By: Relevance
“…A majority of hospitalized patients requiring therapy in ICUs were adults <65 years who on admission had respiratory failure due mainly to primary influenza pneumonia in agreement with other observations,8, 15, 21, 22, 23, 24 and in clear contrast to seasonal influenza. The number of patients that are admitted to an ICU may vary related to criteria used by the institution.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A majority of hospitalized patients requiring therapy in ICUs were adults <65 years who on admission had respiratory failure due mainly to primary influenza pneumonia in agreement with other observations,8, 15, 21, 22, 23, 24 and in clear contrast to seasonal influenza. The number of patients that are admitted to an ICU may vary related to criteria used by the institution.…”
Section: Discussionsupporting
confidence: 90%
“…Immediate initiation of oseltamivir treatment potentially reduces the risk of complications and requirement for ICU admission,14 and we observed no difference in time from diagnosis to initiation of antiviral therapy between the second and third wave. In the critically ill patients with pandemic influenza, it has been suggested to increase the dose of oseltamivir to 300 mg daily,15, 16 but this is not supported by clinical data and the pharmacokinetics of oseltamivir 75 mg twice daily in intensive care patients have been demonstrated to be comparable to patients with mild disease 17. The majority of our patients were treated with 150 mg daily.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Hence, early initiation of CRRT before the onset of fluid overload should be considered in patients on ECMO. Blijdorp et al observed that initiating preemptive CRRT during ECMO in neonatal patients improved outcomes by decreasing time on ECMO due to improved fluid management [6,7]. It has also been shown that odds ratio for death was higher when CRRT was started later and longer it was performed.…”
Section: Timing Of Initiation Of Crrt In Ecmo Patientsmentioning
confidence: 98%
“…The ECMO circuit was primed as described elsewhere (23). From 2005 onward, all patients received by protocol preemptive continuous hemofiltration (CH) by placement of a hemofilter (Multiflow 60; Hospal, Lyon, France) parallel to the ECMO circuit and distal to the roller pump.…”
Section: Setting and Participantsmentioning
confidence: 99%